2013
DOI: 10.7314/apjcp.2013.14.4.2649
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Depression in Breast Cancer Survivors: a Systematic Review of Observational Studies

Abstract: Background: Depression is common in breast cancer patients. The aim of this paper was to make a systematic review of its prevalence and associated factors oin breast cancer survivors. Materials and Methods: An extensive systematic electronic review (PUBMED, CINAHL, PsyINFO and Ovid) and handsearch were carried out to retrieve published articles up to November 2012, using Depression OR Dysthymia AND (Cancer OR Tumor OR Neoplasms as the keywords. Information about the design of the studies, measuring scale, char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
128
2
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(144 citation statements)
references
References 53 publications
(79 reference statements)
11
128
2
3
Order By: Relevance
“…Furthermore, a lower level of education is associated with lower income, which also causes stress and other psychological problems (Nik Jaafar et al, 2014). In the literature, studies showed the important role of lower educational status on depression and anxiety (Zainal et al, 2013). In a study conducted by Hong et al (2014), educational level was found to be the major factor in higher levels of depression.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a lower level of education is associated with lower income, which also causes stress and other psychological problems (Nik Jaafar et al, 2014). In the literature, studies showed the important role of lower educational status on depression and anxiety (Zainal et al, 2013). In a study conducted by Hong et al (2014), educational level was found to be the major factor in higher levels of depression.…”
Section: Discussionmentioning
confidence: 99%
“…On average, the prevalence of depression and anxiety among cancer patients ranged from 20 to 30%, according to the study published in Asia Pacific Journal of oncology [13] and BMJ [14]. Where as depression was present in 28.0% of cancer patients and 40.0% of cancer patients had anxiety as per HADS according to a study done in Nepal [15].…”
Section: Resultsmentioning
confidence: 99%
“…Nowadays cancers are leading cause of death around the world (Aghbali et al, 2013) Breast cancer (BC) is one of them with increased incidence, high mortality rate, and high economic and social costs (Zainal et al, 2013). The BC stands for about 30% of cancer-caused deaths in High Income Countries Breast cancer is about 30% cause of cancer deaths in High Income Country.…”
Section: Introductionmentioning
confidence: 99%